Veterinary Clinic Management Application System - Abidin, Muhammad Zulkarnain; Mohd Yusof, Munirah (Applied Information Technology And Computer Science, 2022)
Information systems are seen as important because they are able to increase the efficiency and effectiveness of an organization. In this regard, a veterinary clinic management application system has been developed to facilitate the work process at Kerteh Petz Care (KPC). The purpose of this system developed is to address problems regarding customer data such as loss and repetition of stored data. In addition, the system also makes it easier for customers to use clinic services such as booking appointment slots without having to physically attend the clinic. This system is developed based on a prototype model that emphasizes interaction with potential users. Thus, two prototypes are made and tested together to ensure that the system works according to the prescribed requirements. This system uses Hypertext Preprocessor (PHP) and Dart as the programming language and MySQL database. This application system is divided into two platforms, which is web for the use of clinic staff and applications for the use of clinic customers. Clinic staff can manage the system such as updating user information, reviewing and confirming appointment requests, answering questions in the consultation page as well as generating monthly reports. Meanwhile, clinic customers able to add and view their pet list, book an appointment slot, ask questions or any problems and review their pet treatment records. Finally, the application of this system is expected to help the management of KPC work in running their veterinary business.